(untitled) (Kairaranga, 2017)
This research paper centres on a professional inquiry across Resource Teachers: Learning and Behaviour (RTLB) clusters within New Zealand that explored the role induction played in the ongoing development of new RTLB’s professional identity. A review of the literature was timely as although the RTLB service has the RTLB Toolkit, induction practices vary across the country. There is no ‘set’ framework that all RTLB use, and evolvement of professional identity is not mentioned within the RTLB Toolkit. Through anonymous online surveys to both new RTLB to the service in the last three years, and Practice Leaders (PLs), participants shared key factors they believed supported the development of their professional identity through their induction framework. The research results highlighted six key components of an effective induction process that could foster professional identity growth. They were consistency of induction, clarity and understanding around what is professional identity, developing and maintaining trusting relationships, the importance of ako, Communities of Practice (COP) and the impact of RTLB training on professional identity.